Development of framework for effective project scope management in the Sultanate of Oman for government projects - Qais Hashil Salim, Al Rubaiei (2021)
Managing the variation order cost of projects is a challenge in most countries around the world. Each year, there is a huge amount paid in variation orders, which has burdened approved budgets with extra costs. Many studies have been done in this field to explore the factors which have triggered the issue of variation orders costs increase. The most likely consequences of this issue are the delay of the handovers of projects and the increase in the total costs of the projects. Moreover, this issue places a more significant burden on the approved budgets from the government and consequently may withhold the stakeholders from the project’s main benefits. This research applies a mixed-method approach to investigate and explore the relationship between the variation order costs and project management success factors to develop an effective framework to manage project scope in government projects in the Sultanate of Oman. More than 200 questionnaires were distributed to project department employees in the government ministries, and a total of eight managers in the project departments were interviewed. The empirical results indicated that there is a positive and significant correlation between stakeholder involvement variable, project scope variable, and variation order costs in the Sultanate of Oman government projects. There is a significant and positive relationship between the two variables, which specifies that the improvement in the project scope management process will improve the variation order costs. The framework developed in this study may be used as a measurement tool to control the size of the variation order costs in future projects. The research concluded by proposing the government to use the project scope management framework as well as update the roles and procedures in its project management. The government project management system is a critical field, which requires more attention due to its massive amount of expenses and the need for improvements based on the context of respective countries.